Prevalence and histopathological signatures of optic disc drusen based on microscopy of 1713 enucleated eyes. Issue 2 (1st July 2019) - Skougaard, Marie; Heegaard, Steffen; Malmqvist, Lasse; Hamann, Steffen
Abstract: Purpose: Optic disc drusen (ODD) are calcified optic nerve head deposits. Objectives of this study were to examine the prevalence of ODD in eyes removed by enucleation and to describe related histopathological signatures of ODD and surrounding tissues. Methods: The study was a retrospective observational case series study assessing and re‐evaluating enucleated eyes in Denmark from 1980 to 2015 by microscopy. Individual ODD were described based on size, number and location (superficial and/or deep) within the optic nerve. Optic nerve heads with ODD were assessed for elevated discs, retinal nerve fibre layer (RNFL) thickness, oedematous axons and presence of localized peripapillary axonal distension (LPAD) equivalent to the peripapillary hyperreflective ovoid mass‐like structures seen on optical coherence tomography. Results: Microscopy of 1713 eyes revealed ODD in 31 eyes equivalent to a prevalence of 1.8%. Optic disc drusen (ODD) were seen as circular shapes of different sizes and varying number. Elevated discs were present in 15 (54%) of the cases. Thickening of the superficial RNFL was present in eyes with large deeply located ODD. For more superficial ODD of approximately same size, the RNFL was thinner. Oedematous axons were present in three eyes. Localized peripapillary axonal distension (LPAD) was seen in five eyes. Conclusions: Prevalence of ODD in this study of histopathological signatures was higher than the prevalence found in clinical studies. Our results suggest that large, deep ODD might cause crowding and herniation of axons in the optic nerve head leading to a thickened superficial nerve fibre layer, pseudopapilledema and LPAD.